Establishing comprehensive normative values of objective sleep quantity and quality in collegiate athletes - Vatne, E.; Vatne, M.; Cencer, D.; Kraemer, W. J.; Saenz, C.; Stone, J.; Merrigan, J.; Pulvermacher, K.; Robinson, B.; Dial, M.; Jones, P.; Montalbano, A.; et al. (The Journal of Strength and Conditioning Research, 2025)
Collegiate athletes frequently experience insufficient sleep, adversely affecting physical performance and recovery. Historically, sleep studies primarily relied on subjective data and small sample sizes with most subjects being male athletes, which limits generalizability. Modern wearables enable more robust, objective analysis. Our objective was to leverage wearables to establish normative values for sleep quantity and quality in National Collegiate Athletic Association (NCAA) Division I athletes and investigate sex and sport-specific differences. Retrospective analysis was conducted on 37,672 sleep records from 397 NCAA Division I male and female athletes across 22 sports. Subjects wore a validated wearable device, Oura Ring, nightly for objective sleep tracking. Key metrics included total sleep time (TST), time in bed, sleep efficiency (SE), sleep onset latency (SOL), resting heart rate, and heart rate variability (HRV). Descriptive statistics and Wilcoxon rank-sum tests (p < 0.05) were used to analyze differences by sex and sport. Average TST across athletes was 6.97 ± 1.27 hours. Female athletes achieved significantly higher TST (p < 0.001, effect size (ES) = 0.23), SE (p < 0.001, ES = 0.29), and HRV (p < 0.001, ES = 0.09) than male athletes, while exhibiting shorter SOL (p < 0.001, ES = -0.09). Eight teams averaged <7 hours of TST per night. Findings underscore the need for tailored sleep interventions in collegiate athletes, particularly in male athletes. Strategies include education, monitoring, and scheduling adjustments to enhance recovery and performance.